2017
DOI: 10.1088/1757-899x/180/1/012223
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Athlete 2016 Paralympic Jabar

Abstract: Abstract. This study aims to determine the quality of life of Paralympic athletes who are members in West Java Peparnas Pelatda 2016. The research method is a method of crosssectional descriptive analytical. The population of all the people who have disabilities, the sample is non-athletes and athletes at the Paralympic Pelatda West Java with saturated sampling technique. The instrument used questionnaire WHOQOL-BREF. The results of the analysis and calculation of the data obtained, the four domains: physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…In terms of psychological well-being, the positive impact of practicing sport on athletes with disabilities is consistent [68][69][70]76,79,80]. The perception of psychological well-being seems to have a negative correlation with increasing age and persons with congenital disabilities showed higher well-being scores compared to persons with an acquired disability.…”
Section: Well-beingmentioning
confidence: 63%
See 3 more Smart Citations
“…In terms of psychological well-being, the positive impact of practicing sport on athletes with disabilities is consistent [68][69][70]76,79,80]. The perception of psychological well-being seems to have a negative correlation with increasing age and persons with congenital disabilities showed higher well-being scores compared to persons with an acquired disability.…”
Section: Well-beingmentioning
confidence: 63%
“…Through the systematic review process, we identified twenty-seven studies: twelve from Europe (Italy [66,79], Ireland [68], UK [59,63,78,80], Poland [7], Portugal [74], Turkey [65] and Ukraine [69,70]), ten from North America (USA [47,60,72,73,[81][82][83] and Canada [64,67,75], three from South America (Brazil [61,62] and Chile [77]), one from Asia (Indonesia [76]) and one from Oceania (Australia [71]).…”
Section: Originmentioning
confidence: 99%
See 2 more Smart Citations
“…The facilities and infrastructure in the Extraordinary School are used for the development of the achievements of children with special needs. Based on the phenomenon in the form of fact, researchers only limit to children with special needs who participate in the National Student Paralympic Week (PEPARPENAS) especially the sports of athletics (S. Mudjianto et al, 2017;Sufyar Mudjianto et al, 2018). One of the considerations of limiting this problem in the sport of athletics, especially in central Java because of the limited time, cost, energy, and reach of the subject and the outbreak of Covid_19 disease that panicked people around the world.…”
Section: Introductionmentioning
confidence: 99%